Good clinical practice recommendations for the management of gastroesophageal reflux disease. A Latin American expert review - M.A. Valdovinos-Díaz; A. Hani; C. Defilippi-Guerra; L. Fernando-Pineda; J.M. Remes-Troche; A. Riquelme; L.J. Abrahão-Junior; L. Aguilar-Paiz; C. Almonte-Nuñez; H. Burgos; C. Días; O. Gómez-Escudero; et al. (Revista de Gastroenterología de México (English Edition), 2025)
Introduction and aim: Due to its elevated prevalence, complex pathophysiology, and broad spectrum of clinical manifestations, gastroesophageal reflux disease (GERD) requires precision diagnosis and treatment. The aim of this Latin American expert review was to provide good clinical practice recommendations for the rational use of diagnostic tests and the personalized treatment of GERD. Methods: Good clinical practice recommendations were developed by a group of Latin American experts in GERD. A thorough review of the literature was conducted, and recommendations on the diagnosis and treatment of GERD were issued after three group discussions. Results: Twenty-one experts on GERD formulated 30 clinical recommendations for appropriately indicating diagnostic tests for disease phenotypes and their medical treatment, refractory GERD management, endoscopic and surgical treatment indications, the control of GERD in obesity, pregnancy, and older adults, as well as the role of Helicobacter pylori infection and GLP-1 agonists. Conclusions: Determining GERD phenotypes in patients through the appropriate use of diagnostic tests enables personalized treatment to be prescribed. The recommendations established in this document may contribute to improving the quality of care of patients with GERD. Resumen: Antecedentes: La enfermedad por reflujo gastroesofágico (ERGE) por su elevada prevalencia, fisiopatología compleja y su espectro amplio de manifestaciones clínicas requiere de un diagnóstico y tratamiento de precision. Objetivo: En esta revisión de expertos latinoamericanos se hacen recomendaciones de buena práctica clínica para el uso racional de las pruebas diagnósticas y la prescripción de un tratamiento personalizado de la ERGE. Métodos: Las recomendaciones de buena práctica clínica se generaron por un grupo de expertos en ERGE de Latinoamérica. Se realizó una revisión detallada de la literatura y se emitieron recomendaciones sobre diagnóstico y tratamiento de la ERGE después de 3 discusiones en grupo. Resultados: Veintidós expertos en ERGE elaboraron 30 recomendaciones de buena práctica clínica para la indicación apropiada de pruebas diagnósticas y tratamiento médico de los fenotipos de la enfermedad, el manejo de la ERGE refractaria, indicaciones de tratamiento quirúrgico y endoscópico, y el control de la ERGE en obesidad, embarazo, adulto mayor y el papel de la infección por Helicobacter pylori y agonistas de GLP-1. Conclusiones: La fenotipificación del paciente con ERGE con el uso apropiado de pruebas diagnósticas permite la prescripción de un tratamiento personalizado. Las recomendaciones establecidas en este documento pueden contribuir a mejorar la calidad de atención del paciente con ERGE.